Equilibrium Grading Policies With Implications for Female Interest in STEM Courses - Ahn, Tom; Arcidiacono, Peter; Hopson, Amy; Thomas, James (Econometrica, 2024)
We show that stricter grading policies in STEM courses reduce STEM enrollment, especially for women. We estimate a model of student demand for courses and optimal effort choices given professor grading policies. Grading policies are treated as equilibrium objects that in part depend on student demand for courses. Differences in demand for STEM and non‐STEM courses explain much of why STEM classes give lower grades. Restrictions on grading policies that equalize average grades across classes reduce the STEM gender gap and increase overall enrollment in STEM classes.